Metal fabrication technology for agriculture - Jeffus, Larry (Thomson/Delmar Learning, 2004)
Metal Fabrication Technology for Agriculture presents readers with a fast-paced, yet easy-to-understand introduction to must-know welding processes and techniques. Focusing squarely on agricultural welding applications, each section of this full-color book begins by introducing readers to the equipment and materials to be used in the process. Complete instructions for setup in preparation for welding are also included. Remaining chapters in the section allow readers to concentrate on mastering individual welding techniques in various applications and positions. Extensive coverage of brazing and specialized nonmetallic fabrication is designed to lead readers step-by-step in developing the skills necessary for welding all types of agricultural machinery. Up close shots of actual welds and proven-effective learning aids have also been built into every chapter, making this how-to and reference manual a key resource for today's farmers, ranchers, and students participating in agriculture education programs throughout the country.